2017
DOI: 10.1111/ffe.12669
|View full text |Cite
|
Sign up to set email alerts
|

In‐phase and out‐of‐phase thermomechanical fatigue behavior of 4Cr5MoSiV1 hot work die steel cycling from 400 °C to 700 °C

Abstract: The hysteresis loops, stress and strain behavior, lifetime behavior and fracture characteristic of 4Cr5MoSiV1 hot work die steel at a wide range of mechanical strain amplitudes (from 0.5% to 1.3%) during the in-phase (IP) and out-of-phase (OP) thermomechanical fatigue (TMF) tests cycling from 400°C to 700°C under full reverse strain-controlled condition were investigated. Stress-mechanical strain hysteresis loops of 4Cr5MoSiV1 steel are asymmetric, and stress reduction appears at high-temperature half cycles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, many cracks with different lengths are visible in the specimens TMF_02 and TMF_08. In Zuo et al, 12 it was shown that under TMF loading, a great number of cracks are visible, which connects with the observations in the work.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, many cracks with different lengths are visible in the specimens TMF_02 and TMF_08. In Zuo et al, 12 it was shown that under TMF loading, a great number of cracks are visible, which connects with the observations in the work.…”
Section: Discussionsupporting
confidence: 85%
“…With higher stress amplitudes, the crack behaviour changes from intercrystalline to transcrystalline. Another hot-work steel was investigated under strain-controlled IP and out-of-phase (OP) TMF tests in Zuo et al 12 The investigations of the 4Cr5MoSiV1 steel showed that the lifetime under OP TMF is lower than IP TMF and the cracks, which occur, are fewer but larger at IP TMF tests than OP TMF tests.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of hardness from initially 47 to 33 HRC was observed in [19] in a superficial region with a depth of 0.3 mm of a hot forging tool made from martensitic steel X40CrMoV5-1, being a preferred site for the nucleation and propagation of fatigue cracks. Continuous softening of the hot work steel 4Cr5MoSiV1 was observed in [20] in strain-controlled in-phase (IP) and out-of-phase (OP) TMF tests in the temperature range from 400 to 700 • C. Due to softening, the stress levels decrease in the entire temperature range with an increasing number of cycles. Softening in the martensitic steels is attributed to two mechanisms, namely thermal softening controlled by temperature, e.g., analyzed in [21][22][23], and cyclic softening controlled by cyclic plasticity, e.g., analyzed in [24] and in the review article by Jilg [25].…”
Section: Softening Mechanisms In Martensitic Steelsmentioning
confidence: 99%